On the minimal mass blow-up solutions for the nonlinear Schrödinger equation with Hardy potential. (August 2020) - Pan, Jingjing; Zhang, Jian
Abstract: This paper deals with the blow-up solutions of the nonlinear Schrödinger equation with Hardy potential. In terms of the existence for the minimal mass blow-up solutions and the refined compactness lemma, we get precise concentration result of the minimal mass blow-up solutions for the Cauchy problem.